2013
DOI: 10.1128/iai.01195-12
|View full text |Cite
|
Sign up to set email alerts
|

Leptospiral LruA Is Required for Virulence and Modulates an Interaction with Mammalian Apolipoprotein AI

Abstract: dLeptospirosis is a worldwide zoonosis caused by spirochetes of the genus Leptospira. While understanding of pathogenesis remains limited, the development of mutagenesis in Leptospira has provided a powerful tool for identifying novel virulence factors. LruA is a lipoprotein that has been implicated in leptospiral uveitis as a target of the immune response. In this study, two lruA mutants, M754 and M765, generated by transposon mutagenesis from Leptospira interrogans serovar Manilae, were characterized. In M75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…The lack of involvement in disease pathogenesis by the majority of exoproteins is in agreement with the findings of previous studies on L. interrogans virulence genes which have demonstrated that the majority of genes are dispensable for virulence (27,68). Moreover, with the exception of a catalase gene (katE) (34) and a collagenase gene (24), the genes that have been demonstrated to be essential for virulence, such as HtpG (63), Loa22 (69), and those involved in motility (11,12), LPS biosynthesis (13), heme metabolism (70), and adhesion (71,72), have orthologues in the nonpathogenic species L. biflexa. In combination with the finding that the majority of L. interrogans exoproteins have orthologues in L. biflexa, this evidence further supports the theory that L. interrogans evolved from L. biflexa.…”
Section: Discussionmentioning
confidence: 67%
“…The lack of involvement in disease pathogenesis by the majority of exoproteins is in agreement with the findings of previous studies on L. interrogans virulence genes which have demonstrated that the majority of genes are dispensable for virulence (27,68). Moreover, with the exception of a catalase gene (katE) (34) and a collagenase gene (24), the genes that have been demonstrated to be essential for virulence, such as HtpG (63), Loa22 (69), and those involved in motility (11,12), LPS biosynthesis (13), heme metabolism (70), and adhesion (71,72), have orthologues in the nonpathogenic species L. biflexa. In combination with the finding that the majority of L. interrogans exoproteins have orthologues in L. biflexa, this evidence further supports the theory that L. interrogans evolved from L. biflexa.…”
Section: Discussionmentioning
confidence: 67%
“…LruC was experimentally demonstrated to be an OM lipoprotein but was not exposed on the bacterial surface, it was located in the inner leaflet of the OM ( 84 ). In contrast, LruA was exposed on the leptospiral surface, with a possible role in the modulation of interactions with human apolipoprotein A-I (ApoA-I), contributing to leptospiral virulence ( 86 ). Furthermore, LruA was shown to be essential for L. interrogans virulence in the hamster model ( 86 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified a number of biological processes that appear to be required for leptospiral virulence. These include genes involved in motility (30,36), heme utilization (18), lipopolysaccharide biosynthesis (40), stress resistance (25,41,42), and the host-pathogen interaction (43) and genes that are involved in a manner that has not yet been determined (44,45). However, previous research has also negated the requirement of putative virulence factors LipL32 (46), LipL41 (47), and LigB (48) in the animal infection model.…”
Section: Fig 4 the Lb139mentioning
confidence: 94%